Convergence acceleration of Fourier series revisited - Anry Nersessian (National Academy of Sciences of Armenia)
A generalization of the Krylov-Eckho method is investigated for removing of the classical Gibbs phenomenon. Convergence acceleration scheme for Fourier expansions of piecewise smooth functions is derived. Numerical results are presented and discussed.
Keywords: Approximations and expansions